The crown of Columbus - Dorris, Michael A. 1945-1997; Erdrich, Louise 1954- (HarperCollins, 1991)
The adventures of a pair of mismatched lovers and their quest for the truth about Christopher Columbus.
Keywords: Colomb, Christophe <1450?-1506> - Romans; Columbus, Christopher -- Fiction; Historians -- United States -- Fiction; USA; Fiktionale Darstellung; Historical fiction